Inequitable job accessibility across educational and hukou groups in Beijing: An analysis of transit-based accessibility to sectoral jobs - Sun, Tieshan; Fan, Yingling (Journal of Transport and Land Use, 2018)
This paper documents inequitable transit-based accessibility to sectoral jobs among population groups with different educational attainment and hukou status in Beijing, China. A cumulative transit-based job accessibility measure is applied and multiple data sources are used, including the transit travel-time data from a Chinese web mapping service and the population and employment distribution data from the 2010 Population Census and the 2013 Economic Census of Beijing. We find clear differences in transit-based job accessibility among employment sectors and among population groups in Beijing. On average, jobs in the finance sector are the most accessible by transit, and jobs in the manufacturing sector are the least accessible by transit. Despite having the highest transit dependency, the low-educated migrant population has the lowest transit-based job accessibility regardless of employment sectors. The disparities are especially large when tying specific populations with specific sectors. Within 60 minutes, the low-educated migrant population using transit, on average, can only access 4.6% of total manufacturing jobs in Beijing. In contrast, the same measure for the highly educated local population accessing jobs in the finance sector is as high as 48.3%. The findings suggest that general transit improvements and jobs and population redistribution efforts, without specific sectoral and population considerations, are unlikely to create equal access to job opportunities. In Beijing, greater attention must be paid to connect the low-educated migrant population to low-skilled and decentralized jobs in the manufacturing, construction, and transportation and storage sectors.